ANALISIS METODE SELEKSI (ONLINE DAN OFFLINE) TERHADAP KUALITAS KARYAWAN - Khofifah, Siti Nur; Ikhram W., M. Abdi Dzil (Jurnal Kewirausahaan dan Inovasi, 2022)
The Covid-19 pandemic and the advancement of technology have made companies test jobseekers online. This method is helpful for companies as it does not require direct meetings with the candidates, as well as saving cost and time. However, there companies who still do the recruitment offline due to poor facilities and low readiness in facing changes. One of the companies shifting from offline to inline recruitment is PT. XYZ. The objectives of this research are, first, to identify the online and offline recruitment process conducted by the company, to determine the best recruitment method, and to identify ways to reduce cheating during the selection process, and, second, to measure the quality of hires obtained from online and offline methods. The company has accomplished 80% of the online selection; the stages are different according to the need of the assessment for every position. The qualities of employees hired from online and offline recruitment are equal. The quality of the employees is not seen from the recruitment process, either online or offline, but from the quality of hire.